Comparative effectiveness and safety of Chinese medicine belly button application for childhood diarrhea: a Bayesian network meta-analysis of randomized controlled trials - Bu, Zhi-jun; Liu, Yan-ni; Shahjalal, Md.; Zheng, You-you; Liu, Cheng-jiang; Ye, Meng-meng; Xu, Jin-yang; Peng, Xin-yao; Wang, Xue-hui; Chen, Xu; Liu, Jian-ping; Liu, Hui-lan; et al. (Frontiers in Pediatrics, 2023)
Background: Chinese medicine belly button application (CMBBA) has been used to treat childhood diarrhea (CD) in several randomized controlled trials (RCTs), but its effectiveness and combination strategy still need to be clarified. Therefore, we aimed to evaluate the effectiveness, safety, and the optimal combination strategy of CMBBA in treating CD. Methods: Up until January 2023, we searched for studies that met our inclusion criteria in six databases, including PubMed, the Cochrane Library, Chinese SinoMed, CNKI, VIP, and Wanfang. Heterogeneity was quantified using I2 statistics. A methodological evaluation was performed using the Cochrane Risk Bias Tool 2.0. The Confidence in Network Meta-Analysis online software was employed to evaluate evidence grading. A minimally contextualized framework was used to provide a comprehensive conclusion for the network meta-analysis. Results: We analyzed data from 33 RCTs that included 4,490 children with diarrhea. In terms of clinical effectiveness, CMBBA plus montmorillonite powder plus anti-infectives may be the most effective treatment option for children with diarrhea and concurrent infection according to a minimally contextualized framework. Either exclusive use of CMBBA or CMBBA in combination with modern medicine was beneficial in reducing the time to diarrhea disappearance (MD = -1.33 days, 95% CI: -1.59 to -1.08, Z = -10.103, p< 0.001) compared to modern medicine exclusively, and the difference was statistically significant. The combined usage of CMBBA could shorten the recovery time of dehydration by an average of 0.74 days (MD = -0.74 days, 95% CI: -1.10 to -0.37, Z = -3.931.103, p< 0.001). While some studies have reported mild allergic reactions and mild abdominal pain after CMBBA use, these symptoms can be cured in a relatively short period of time. Conclusions: The combination of CMBBA, montmorillonite powder, and anti-infectives may provide superior clinical effectiveness for children with diarrhea and concurrent infection. To treat CD, CMBBA can be used effectively and safely. However, the findings must be interpreted with cautiously due to the limited number of clinical trials and the low quality of the studies. In addition, the choice of treatment plan should also be based on the specific conditions of each patient.